Deep eutectic solvents (DES) based on sulfur as alternative lubricants for silicon surfaces - Antunes, Mónica (2019)
Deep eutectic mixtures composed of hydrogen-bond donors (HBDs) and hydrogen-bond acceptors (HBAs), the so-called DESs, have recently being proposed as possible “green” alternatives to mineral oils and ionic liquids (ILs) in the lubrication of steel surfaces. DESs have similar physical properties to ILs but have the advantage of being cheaper and easier to prepare. In this work, new DESs containing sulfur units in their composition were prepared and tested in the lubrication of silicon surfaces which are relevant for nano/microelectromechanical systems (NEMS/MEMS). The following new DESs were prepared: ethyldibutyl sulfonium ethylsulfate: polyethylene glycol ([S4,4,2][EtSO4]:PEG), 1-ethyl-tetrahydrothiophenium ethylsulfate: polyethylene glycol ([C2-THT][EtSO4]:PEG), 1-ethyl-3-methylimidazolium (S)-camphorsulfonate: polyethylene glycol ([C2MIM][(S)CSA]:PEG), and 1-methyl-3-picolinium methyl sulfate: polyethylene glycol ([C1-3-pic][MeSO4]:PEG). Other DES, already reported, were tested for comparison purposes: tetrabutylammonium bromide: sulfolane ([N4,4,4,4][Br]:Sulf), choline chloride: polyethylene glycol (ChCl:PEG), and tetrabutylammonium bromide: polyethylene glycol ([N4,4,4,4][Br]:PEG). All DESs were characterized in terms of their water content, viscosity, wettability, and tribological properties. The friction coefficients were measured in a nanotribometer using steel spheres against Si surfaces. The new DES prepared from salts based on the sulfur-containing anions showed good tribological performance, but the best results were obtained with [C2MIM][(S)-CSA]:PEG and [C1-3-pic][MeSO4]:PEG which reduced the friction coefficients to values <0.1, typical of excellent lubrication conditions.